PENGARUH ZUMBA TERHADAP PENURUNAN BERAT BADAN DAN INDEKS MASSA TUBUH PADA ANGGOTA SENAM ZUMBA DI BARATA FITNESS CENTRE BANDA ACEH - Teuku Aditya Kemal; Iziddin Fadhil (Jurnal Sains Riset, 2021)
Zumba is a combination of fast and slow movements using music. Sufficient physical activity such as Zumba is needed to burn excess calories in order not to cause problems like obesity and overweight which can be a major risk of non-communicable diseases. This study aims to assess the effect of Zumba on weight loss and body mass index on Zumba members at Barata Fitness Center Banda Aceh. The pre-experiment research with The One Group Pratest Posttest design was conducted at Barata Fitness Center Banda Aceh on 30 respondents for one month which was taken using purposive sampling technique. The results of this study indicate the significance of the Zumba dance influence on Weights loss (P = 0.000) and body mass index (P = 0.000) at P0.05. The conclusions of this study indicate there is a significant effect between zumba on weight loss and body mass index.Keywords: weight, body mass index, zumba